Penerapan Projek Penguatan Profil Pelajar Pancasila (P5) dalam Implementasi Kurikulum Merdeka di Sekolah Al-Ikhlas Surabaya - Saniyyah Jayusman; M Chuluq Maushuli; Nabila Fitriananda; Fathur Rohman (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyze the implementation of P5 at Al-Ikhlas Elementary School, Surabaya, including planning, module development, project implementation, and supporting factors and obstacles encountered. The study used a qualitative approach with a case study method. Data were collected through observation, interviews, and documentation, then analyzed descriptively qualitatively through the process of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the implementation of P5 at Al-Ikhlas Elementary School, Surabaya has been running well through various projects that represent the dimensions of the Pancasila Student Profile, namely faith and devotion to God Almighty and noble character, global diversity, mutual cooperation, independence, creativity, and critical reasoning. The project implementation uses the Project-Based Learning (PjBL) model with teachers acting as facilitators in the planning, implementation, and evaluation processes of the project. The successful implementation was supported by school commitment, teacher innovation, the availability of facilities and infrastructure, and high student motivation. However, the implementation of P5 still faces challenges such as limited time, module development, project evaluation, and funding. Therefore, strengthened planning and resource support are needed to optimize P5 implementation in elementary schools.